Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6cc03904a
|View full text |Cite
|
Sign up to set email alerts
|

An iron–oxygen intermediate formed during the catalytic cycle of cysteine dioxygenase

Abstract: Combined spectroscopic, kinetic and computational studies provide first evidence of a short-lived intermediate in the catalytic cycle of cysteine dioxygenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 27 publications
8
93
0
5
Order By: Relevance
“…Supporting computational modeling of the transient UV-visible spectra suggest that this transient species is consistent with a cyclic [Fe-O-O-S Cys ]-structure with a quintet ( S = 2) spin state. However, rapid freeze-quench Mössbauer experiments were unable to corroborate this assignment [22]. Therefore, direct spectroscopic validation of the transient intermediate produced during native catalysis is absent.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting computational modeling of the transient UV-visible spectra suggest that this transient species is consistent with a cyclic [Fe-O-O-S Cys ]-structure with a quintet ( S = 2) spin state. However, rapid freeze-quench Mössbauer experiments were unable to corroborate this assignment [22]. Therefore, direct spectroscopic validation of the transient intermediate produced during native catalysis is absent.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate could not be further characterized, but time-dependent density functional theory (TD-DFT) calculations predict it to be the peroxo-bridged intermediate that precedes the ferryl oxo/sulfoxide. 29 …”
Section: Introductionmentioning
confidence: 99%
“…structure A in Figure 3) of cysteine-bound CDO but only the cysteine-CDO would go through the dioxygenation reaction under the appropriate conditions. 82 It was observed that when an anaerobic cysteinebound CDO was titrated with oxygenated buffer at 4°C in a glove-box, this led to the appearance of two absorption peaks at 500 and 640 nm. These peaks were found to scale linearly with concentration of CDO as well as the amount of dioxygen supplied.…”
Section: Short-lived Iron-dioxygen Complex In Cdo Enzymesmentioning
confidence: 99%
“…82 Unfortunately, the intermediate decays in 20 ms and attempts to characterize a short-lived species further, failed, and no indistinguishable EPR and Mössbauer spectra were obtained. Therefore, we resorted to a computational study at the time dependent-density functional theory (TD-DFT) and complete active space -self consistent field (CASSCF) level of theory to establish the nature of the intermediate.…”
Section: Short-lived Iron-dioxygen Complex In Cdo Enzymesmentioning
confidence: 99%
See 1 more Smart Citation